2003
DOI: 10.1074/jbc.m303119200
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-stimulated Protein Kinase C-δ Kinase Activation, Tyrosine Phosphorylation, and Translocation Are Mediated by Src Tyrosine Kinases in Pancreatic Acinar Cells

Abstract: Protein kinase C-␦ (PKC-␦) is involved in growth, differentiation, tumor suppression, and regulation of other cellular processes. PKC-␦ activation causes translocation, tyrosine phosphorylation, and serine-threonine kinase activity. However, little is known about the ability of G protein-coupled receptors to activate these processes or the mediators involved. In the present study, we explored the ability of the neurotransmitter/hormone, CCK, to stimulate these changes in PKC-␦ and explored the mechanisms. In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 68 publications
(147 reference statements)
7
65
2
Order By: Relevance
“…1, B and D, hGH induced a robust tyrosine phosphorylation of c-Src. This effect was abolished by 10 M PP2, a specific inhibitor of Src kinases (20,48,57,61), which has been shown to be without effect on JAK2 activation induced by hGH (20,61 Fig. 2A), consistent with previous findings (60).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…1, B and D, hGH induced a robust tyrosine phosphorylation of c-Src. This effect was abolished by 10 M PP2, a specific inhibitor of Src kinases (20,48,57,61), which has been shown to be without effect on JAK2 activation induced by hGH (20,61 Fig. 2A), consistent with previous findings (60).…”
Section: Resultssupporting
confidence: 80%
“…Means Ϯ SE derived from 3 separate experiments for each are shown (*P Ͻ 0.05 for a chance difference by ANOVA). [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], were cultured in RPMI 1640 tissue culture medium containing 10% (vol/vol) FBS, 100 IU/ml penicillin, and 100 g/ml streptomycin. The BRIN-BD11 ␤-cell line was established by electrofusion of RINm5F insulinoma cells with New England Deaconess Hospital (NEDH) rat pancreatic islet cells and shares the major features of normal pancreatic ␤-cells (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies reported that rottlerin acts on additional targets besides PKCy (40)(41)(42)(43)(44)(45)(46). For example, rottlerin acts as a mitochondrial uncoupler independent of its effects on PKCy (40,43,46).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have shown that tyrosine phosphorylation of PKC␦ in response to various stimuli regulates its subcellular localization as well as other aspects of its function (9,27,(33)(34)(35)(36)(37)(38)(39)(40). To explore a potential role for tyrosine phosphorylation in regulating binding of importin-␣ to PKC␦ in response to H 2 O 2 , we first examined the kinetics of tyrosine phosphorylation of PKC␦ in response to H 2 O 2 using a pan phospho-tyrosine antibody (4G10).…”
Section: Regulated Binding Of Importin-␣ To Pkc␦ In Response Tomentioning
confidence: 99%